How to Control Component Ratio of Conducting Polymer Blend for Organic Photovoltaic Devices by Annealing - Bobins Augustine; Tapio Fabritius (International Journal of Photoenergy)
There are various conducting polymer blends which are used as hole transporting layers (HTL) in organic photovoltaic devices (OPV). The electrical performance of these conducting polymer blends depends crucially on its surface compositions and morphology. In this paper, we studied poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) or PEDOT:PSS as an example of the HTL conducting polymer blends used in OPV. We have investigated the effect of annealing PEDOT:PSS in different atmospheres such as vacuum, N2, and air at different temperatures. It was found that the component ratio of the polymer blend is changing with annealing temperature and atmosphere. PSS/PEDOT ratio was found to have clear influence on the electrical performance of the material. In practice, we found that annealing can be used as a method to control component ratio of the HTL conducting polymer blend to achieve better electrical performance in OPV devices. The component ratio changes of the polymer with annealing were understood by X-ray photoelectron spectroscopy (XPS). Annealing in N2 atmosphere at 220°C for 1 hour gave best electrical performance for the polymer and the PSS/PEDOT ratio at that condition was close to 1.1, while the initial ratio was 2.5. Optimizing HTL layer by simple conductivity measurement does not guarantee best performance in OPV since surface property changes during annealing might affect the deposition of successive active layers on top and thus final device. Thus we have optimized annealing condition of the HTL layer according to the OPV performance itself.